Allometric and temporal scaling of movement characteristics in Galapagos tortoises. (21st July 2016) - Bastille‐Rousseau, Guillaume; Yackulic, Charles B.; Frair, Jacqueline L.; Cabrera, Freddy; Blake, Stephen
Summary: Understanding how individual movement scales with body size is of fundamental importance in predicting ecological relationships for diverse species. One‐dimensional movement metrics scale consistently with body size yet vary over different temporal scales. Knowing how temporal scale influences the relationship between animal body size and movement would better inform hypotheses about the efficiency of foraging behaviour, the ontogeny of energy budgets, and numerous life‐history trade‐offs. We investigated how the temporal scaling of allometric patterns in movement varies over the course of a year, specifically during periods of motivated (directional and fast movement) and unmotivated (stationary and tortuous movement) behaviour. We focused on a recently diverged group of species that displays wide variation in movement behaviour – giant Galapagos tortoises ( Chelonoidis spp.) – to test how movement metrics estimated on a monthly basis scaled with body size. We used state‐space modelling to estimate seven different movement metrics of Galapagos tortoises. We used log‐log regression of the power law to evaluate allometric scaling for these movement metrics and contrasted relationships by species and sex. Allometric scaling of movement was more apparent during motivated periods of movement. During this period, allometry was revealed at multiple temporal intervals (hourly, daily and monthly), with values observed at daily and monthly intervals corresponding most closely to the expected one‐fourth scaling coefficient, albeit with wide credible intervals. We further detected differences in the magnitude of scaling among taxa uncoupled from observed differences in the temporal structuring of their movement rates. Our results indicate that the definition of temporal scales is fundamental to the detection of allometry of movement and should be given more attention in movement studies. Our approach not only provides new conceptual insights into temporal attributes in one‐dimensional scaling of movement, but also generates valuable insights into the movement ecology of iconic yet poorly understood Galapagos giant tortoises. Abstract : Allometric scaling of home‐range size has been much studied and is generally predictable but one‐dimensional movement metrics scale more consistently with body size. Yet, evaluating movement parameters in one‐dimensional space requires a priori definition of a temporal scale. The authors illustrate the importance of scale using movement of giant Galapagos tortoises.